2023
DOI: 10.1002/anie.202217253
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated 2D Layered and Nonlayered Metal Phosphorous Trichalcogenides Nanosheets as Promising Electrocatalysts for CO2 Reduction

Abstract: Two-dimensional (2D) materials catalysts provide an atomic-scale view on a fascinating arena for understanding the mechanism of electrocatalytic carbon dioxide reduction (CO 2 ECR). Here, we successfully exfoliated both layered and nonlayered ultra-thin metal phosphorous trichalcogenides (MPCh 3 ) nanosheets via wet grinding exfoliation (WGE), and systematically investigated the mechanism of MPCh 3 as catalysts for CO 2 ECR. Unlike the layered CoPS 3 and NiPS 3 nanosheets, the active Sn atoms tend to be expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…have been explored as HER electrocatalysts and have received a great deal of attention due to their easily exfoliated layered structure, abundant active sites, and high chemical stability. [20][21][22][23] Despite the relatively poor intrinsic activity of these compounds reported earlier, their properties can be largely improved by chemical exfoliation, elemental doping, and compositing with reduced graphene oxide. [24][25][26] Moreover, it is well known that the HER activity of single-component catalysts can be improved by constructing heterojunctions consisting of two or more different compounds.…”
Section: Introductionmentioning
confidence: 99%
“…have been explored as HER electrocatalysts and have received a great deal of attention due to their easily exfoliated layered structure, abundant active sites, and high chemical stability. [20][21][22][23] Despite the relatively poor intrinsic activity of these compounds reported earlier, their properties can be largely improved by chemical exfoliation, elemental doping, and compositing with reduced graphene oxide. [24][25][26] Moreover, it is well known that the HER activity of single-component catalysts can be improved by constructing heterojunctions consisting of two or more different compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HAADF‐STEM results suggest that the prepared nanosheets have a crystal structure consistent with previous reports (Figure 2h). [ 14 ] We also observed that the prepared nanosheets have point defects (Figure 2i), which is conducive to improving the photothermal conversion. [ 20 ] Figure 2j shows the results of STEM electron energy‐loss spectroscopy (EELS) maps, which reveal the presence of Ni, P, S, and C in Ni10P1, providing direct evidence for the successful preparation of the NiPS 3 /PVA nanocomposites.…”
Section: Resultsmentioning
confidence: 87%
“…As the typical MPCh 3 material, NiPS 3 nanosheet dispersions in organic solvents such as isopropanol (IPA) have attracted widespread attention, [ 14 ] and its small band gap (≈1.42 eV) [ 15 ] offers potential for photothermal conversion. The deposition of additives on the surface of 2D materials is an effective method to enhance their stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being used as an electrocatalyst for water splitting, MPS 3 -based catalysts can be developed for oxidation/reduction reactions, for example, CO 2 reduction, 107 nitrogen reduction, etc . However, the existing research is still at an early stage.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%